Studi Kandungan Logam Berat Tembaga (Cu) pada Air, Sedimen, dan Kerang Darah (Anadara granosa) di Perairan Sungai Sayung dan Sungai Gonjol, Kecamatan Sayung, Kabupaten Demak - Cahyani, Maryuli Dyah; Nuraini, Ria Azizah Tri; Yulianto, Bambang (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Study of copper (Cu) content in water, sediment, and Blood Clam (Anadara granosa) was conducted in coastal waters of Bedono, District Sayung, Demak district in 2010 and 2011. This study was done because coastal waters of Bedono (such as rivers and river Sayung Gonjol) functioned as the disposal trajectory by the industrial area located along the highway Semarang - Demak. This study aimed to analyze the heavy metal content of Cu in coastal waters and Rivers Sayung and River Gonjol, District Sayung, Demak. The study was conducted during low tide conditions (in 2010) and high tides (in 2011). The results showed that in 2010, the copper content in water of River Sayung ranged from 0.003 to 0.056 mg/l, whereas in the River Gonjol, copper content ranged from not detected - 0.026 mg/l. In 2011, copper content in water is not detected, either in the River Sayung and in the River Gonjol. Copper content in the sediment of River Sayung ranged from 4.89 to 28.75 mg/kg, and in River Gonjol from 18.77 to 71.28 mg/kg (in 2010). In 2011, copper content in the sediment of mouth of River Sayung ranged from 16.1 to 25.57 mg/kg, and in the mouth of River Gonjol ranged from 16.69 to 52.72 mg/kg. In 2010, copper content in the soft tissues of the blood clam in the mouth of River Sayung was 29.86 mg/kg, and at 31.2 mg/kg in the mouth of River Gonjol. Meanwhile, in 2011, copper content was not detected in blood clams. Overall, copper content in water, sediment, and blood clams were still below the threshold quality standard set by each authority.